Psychophysiological processes, ensuring the achievement of sports results - Yu. E. Vaguine (National Electronic Information Consortium (NEICON), 2021)
Objective: to investigate the role of psychophysiological processes in achieving sports results.Materials and methods: the driving force of sports behavior was measured in freedivers, basketball players and athletes, which consisted of motivation to achieve sports results, emotional stress, situational information, hypoxic stability, and physical endurance. Then the sportsmen rotated the pedals of the bicycle ergometer with simultaneous intermittent breath holdings from 20 to 60 s.Results: it has been established that all components of the driving force of behavior are necessary for the sports activity of all groups of sportsmen. For the driving force of freedivers' behavior, hypoxic stability is of greatest importance (r = 0.59), for basketball players - emotional stress (r = 0.6) and for athletes - emotional stress and situational information (r = 0.71 and 0.58). In addition, hypoxic stability and physical endurance directly affect the final sports result (r = 0.7 and 0.65) in conjunction with the driving force of behavior (r = 0.53).Conclusion: sports result is provided by the driving force behind the behavior of sportsmen. For freedivers, hypoxic stability is of primary importance, for basketball players - physical endurance and emotional stress, and for athletes - the totality of all components of the driving force of behavior.